NETosis-Forming Ability of Neutrophils in Patients with Limited and Disseminated Tuberculous Lesions - A. V. Mordyk; A. N. Zolotov; D. G. Novikov; N. A. Kirichenko; P. O. Pakhtusova; A. O. Ptukhin (Туберкулез и болезни лёгких)
The objective: to assess NETosis-forming ability of neutrophils in patients with limited and disseminated tuberculous lesions.Subjects and Methods. 44 new cases of respiratory tuberculosis were included in the study. Group 1 consisted of 22 patients with limited focal or infiltrative tuberculosis with no lung tissue destruction, Group 2 included 22 patients with disseminated tuberculosis with destruction of the lung tissue. Control Group (Group 0) included 22 healthy volunteers. NETosis-forming ability was assessed in vitro in the isolated fraction of neutrophils from peripheral venous blood. The ratio (%) of neutrophils of different degrees of activation and the ratio (%) of various forms of neutrophil extracellular traps (NET), the bacterial capture coefficient of NEL were calculated.Results. NETosis-forming ability of neutrophils in the patients from Groups 1 and 2 was more pronounced versus Group 0, and in Group 2 it was maximum. In Group 2, the bacterial capture rate by NET was statistically significantly lower versus Group 1 (p=0,0147), which may indicate some degree of «inferiority» of NET formed in Group 2.